Distinct Effects of the Two Strong El Niño Events in 2015–2016 and 1997–1998 on the Western North Pacific Monsoon and Tropical Cyclone Activity: Role of Subtropical Eastern North Pacific Warm SSTA. Issue 5 (20th May 2018) - Wu, Yi‐Kai; Hong, Chi‐Cherng; Chen, Cheng‐Ta
Abstract: Western North Pacific (WNP) summer monsoon and tropical cyclone (TC) activity are supposed to be declined during a strong El Niño decaying summer. The 2015–2016 event, which had a Niño 3.4 sea surface temperature (SSTA) similar to the 1997–1998 event, was classified as a strong El Niño. However, WNP summer monsoon and TC activity were normal or even stronger than the climatological mean during the decaying summer. This study addressed why the 2015–2016 El Niño event exerted distinct effects on the WNP's climate compared with the 1997–1998 event. The major difference in oceanic conditions between the two events is that a southwest‐northeast‐tilted subtropical warm SSTA in the eastern North Pacific associated with a pronounced westerly anomaly in the subtropical North Pacific was observed in 2015–2016. Singular value decomposition (SVD) analysis of the covariance of the SSTA and low‐level wind indicated that second mode, resembling the Pacific meridional mode (PMM), accounted for the subtropical warm SSTA in the eastern North Pacific. Conversely, the contribution of leading mode (i.e., El Niño SSTA) was insignificant. Observational analysis indicated that the PMM‐associated SSTA is significantly correlated with a large‐scale low‐level cyclonic circulation anomaly in the WNP during the El Niño decaying spring to summer, which may have an effect on offsetting the El Niño‐induced anticyclone in the WNP and therefore returns WNP summer monsoon and TC activity to normal. The PMM‐SST correlated with cyclonic circulation anomaly was further enhanced by an active phase of intraseasonal oscillation. The possible effect of PMM‐associated SST on the summer monsoon and TC activity was further supported by numerical experiments. Plain Language Summary: Western North Pacific (WNP) summer monsoon and tropical cyclone (TC) activity are supposed to be declined during a strong El Niño decaying summer. The 2015–2016 event, which had a Niño 3.4 sea surface temperature (SST) anomaly similar to the 1997–1998 event, was classified as a strong El Niño. However, WNP summer monsoon and TC activity were normal and even stronger than the climatological mean during the decaying summer. This study addressed why the 2015–2016 El Niño event exerted distinct effects on the WNP's climate compared with the 1997–1998 event. We demonstrated the distinct impacts in the two strong El Niños are primarily attributed to the oceanic forcing of the subtropical warm SST in the eastern North Pacific. Key Points: Distinct impacts of the two strong El Niño events, 1997–1998 and 2015–2016, on the summer monsoon and TC activity in the WNP were documented SVD analysis reveals that the SVD2, a subtropical SST resembling the Pacific meridional mode (PMM), contributes to these distinctions The PMM‐like SST may generate a cyclone anomaly in the WNP, which consequently offsets the El Niño‐induced anticyclone in the WNP